Modelo de un escritorio ergonómico e inteligente para instructor/aprendiz en un ambiente de formación automatizado en tiempos de post Covid-19. - Ovalles Pabon, Freddy Oswaldo
Electronic devices in the academic environment within the pandemic and the implementation of automated classrooms have played an important role in guiding training and teaching, generating value within the new condition that are facing educational institutions and homes in our country. This project shows two models of ergonomic and intelligent desks for teacher and student for a modern academic training environment in post pandemic times. The main purpose of the work is to design a model of intelligent and vertical desk for teacher and student in an automated academic training environment in post pandemic times. The research is of qualitative approach with exploratory documentary and experimental type. The methodological design based on Design Thinking was implemented applying its phases Empathy, Definition, Ideation, Prototyping and Testing adjusted to the specific objectives. The fourth specific objective, the 3D modeling of the intelligent and vertical desk for students and teachers, was achieved. The teacher's furniture will have outstanding features such as the inclusion of technological ports, noise reduction of the lifting motor, the resistance of the legs, cup holders and USB charging ports, NFC. On the other hand, the student furniture will have: electric linear actuators, speakers, USB 3.0 Hub, NFC, charging ports and a button to regulate the height. With the collection of information from students and teachers and state of the art documentary base, it was possible to understand the needs evidencing the lack of an intelligent desk in automated classrooms; establishing the need for a piece of furniture for academic alternation in times of pandemic.